Evaluating baddeleyite oxygen isotope analysis by secondary ion mass spectrometry (SIMS) - Davies, J. H. F. L.; Stern, R. A.; Heaman, L. M.; Mose, D. E.; Walton, Erin L.; Vennemann, T. (My University, 2018)
Two baddeleyite megacrysts were evaluated as potential reference materials (RMs) for SIMS oxygen isotope analysis, and utilized to understand and calibrate instrumental mass fractionation (IMF).